Taxation, Law And Socio-Economic Resilience: The Zimbabwe Case - MOYO, PRISCILLA; CHIPETIWA, MARKNOUGHLER (Lighthouse: The Zimbabwe Ezekiel Guti University Journal of Law, Economics and Public Policy, 2024)
The best tax system for any country is presumably one that reflects its economic structure, its capacity to administer taxes, its public service needs and its access to such other sources of revenue (Bird, 2013). Since taxes are the main source of funding for public goods like public infrastructure and law and order maintenance, raising revenue continues to be the most important role of taxes in a world where many governments are dealing with declining revenue, rising expenditures and ensuing fiscal constraints. Tax policy is not just about economics, it is about politics (Moore, 2007). There are several general tax policy concerns that have historically influenced the formation of taxation systems, presuming a particular amount of income that must be produced that depends on the larger economic and fiscal policies of the country concerned. All the changes in the economy brought about by the implementation of tax systems are included in the consequences of taxes (James and Nobes, 2008). Taxation has an impact on several variables, including employment, investment, consumption and output. Governments could not support their societies' needs if they did not collect taxes. The government uses the money it collects from taxes to fund social projects which makes them essential. However, whether in the rich or developing world, tax avoidance and evasion are the double crimes that face and destroy all tax systems. Adhere (2013) asserts that the Zimbabwean situation seems unique when viewed against the scale of corrupt practices prevalent in the country and the detrimental effects of economic sanctions imposed by the West, resulting in the country having to rely on internally generated income for its operations, including, but not limited to, tax collections. To escape from the constraints of tax, corruption, high tax rates and lack of trust on Government and tax authority by taxpayers, are among the reasons for evasion and avoidance (ibid.). This write-up will scour out how taxation laws operate in regulating tax payments and the socioeconomic adaptation thereto.